Diagnosis of a Morgagni-Stewart-Morel Syndrome in a Patient with Ischemic Stroke. Report of a Case - Masleidy Valladares Valle; Juan Ibrahim García Leonard; Ada Sánchez Lozano (Revista Finlay)
Morgagni-Stewart-Morel syndrome is a rare disease characterized by bilateral internal frontal hyperostosis associated with metabolic and psychiatric disorders, arterial hypertension, and dysfunction of the cranial nerves of undefined etiology. The case of a 77-year-old patient with a history of type 2 diabetes mellitus, systemic arterial hypertension and psychiatric disorder, who was admitted to the Neurology Service of the Dr. Gustavo Aldereguía Lima University Hospital in Cienfuegos with dysarthria and right hemiparesis is presented. Diagnostic skull imaging studies were performed where the presence of extensive internal frontal hyperostosis, cortical atrophy and a left thalamic infarction was observed. During his hospital stay, the presence of grade I obesity, hirsutism and hypercholesterolemia was documented. The patient met the criteria for Morgagni-Stewart-Morel syndrome by manifesting the presence of internal frontal hyperostosis with endocrinological and neuropsychiatric manifestations. The case is presented in order to demonstrate the diagnosis of a low incidence disease in ischemic cerebrovascular patients with the presence of symptoms that include several well-documented vascular risk factors.